Professional training of profiler specialists of airport aviation security services (Journal of Educational Sciences, 2023)
The article substantiates the need for special training and training of inspectors-specialists in the aviation security system for psychological profiling. Today, the airports of our country are equipped with sophisticated from a technical point of view, modern tracking systems, identification, facial recognition, detection of explosives and dangerous substances and objects for transportation. All this makes it possible to carry out quality control in controlled areas of the airport. Passenger profiling is not something new for aviation and is actively used by Kazakhstani specialists asan additional method of aviation security. New and evolving threats to aviation security require innovative and proactive solutions. Profiling is a set of psychological methods of rapid diagnostics used to identify a potentially dangerous person. To identify a potentially dangerous person means to determine the profile of a person and classify him as dangerous passengers. The authors of the article prove the assumption that the level of representations and preparedness of employees of Aviation Security Services for psychological profiling increase the effectiveness of their professional activities and positively affect the quality of ensuring the safety of citizens. Based on the survey of students, the most important professional qualities of the profiler inspector were identified. The practical significance of the results lies in the fact that the data obtained make it possible to design the content of training, to focus on the predictive and warning function of profiling.Key words: training of civil aviation specialists, act of unlawful interference (AUI), security, profiling, profiler.